Catalytic CH Bond Addition of Pyridines to Allenes by a Rare‐Earth Catalyst. Issue 23 (21st April 2015) - Song, Guoyong; Wang, Baoli; Nishiura, Masayoshi; Hou, Zhaomin
Abstract The catalytic CH addition of pyridines to allenes has been achieved for the first time by using a half‐sandwich scandium catalyst, thus constituting a straightforward and atom‐economical route for the synthesis of alkenylated pyridine derivatives. The reaction proceeded regio‐ and stereoselectively, affording a new family of alkenylated pyridine compounds which are otherwise difficult to synthesize. A cationic Sc‐η2‐pyridyl species was isolated and confirmed to be a key catalyst species in this transformation.